2009
DOI: 10.1166/jbn.2009.1017
|View full text |Cite
|
Sign up to set email alerts
|

Ionically Crosslinked Chitosan Nanoparticles as Gene Delivery Systems: Effect of PEGylation Degree on <I>In Vitro</I> and <I>In Vivo</I> Gene Transfer

Abstract: The purpose of this work was to develop a new type of nanoparticles made of PEG-grafted chitosans (CS-g-PEG) using tripolyphosphate (TPP) as a polyanionic crosslinker and to investigate the potential of these nanostructures as gene carriers. The formation of these nanoparticles was optimised by the evaluation of the combined effects of pH, PEGylation degree and chitosan/crosslinker ratio on the particle formation. The selected CS-g-PEG/TPP nanoparticles were studied with regard to their physico-chemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 20 publications
2
35
1
1
Order By: Relevance
“…In this work, chitosan nanoparticles were prepared using a well-known preparation method in which the positively charged chitosan is ionically crosslinked with negatively charged TPP-anions. Such chitosan nanoparticles have previously been reported to possess positive zeta potentials [13,[20][21][22][23][24][25][26][27][28][29][30]37], which is in accordance with the results found in this study. But as can be seen in Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this work, chitosan nanoparticles were prepared using a well-known preparation method in which the positively charged chitosan is ionically crosslinked with negatively charged TPP-anions. Such chitosan nanoparticles have previously been reported to possess positive zeta potentials [13,[20][21][22][23][24][25][26][27][28][29][30]37], which is in accordance with the results found in this study. But as can be seen in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Chitosan nanoparticles crosslinked with TPP (chitosan-TPP nanoparticles) have been employed in drug delivery of both small molecular drugs, like estradiol and venlafaxine, and macromolecules, such as insulin and DNA [4,13,17,[19][20][21][22][23][24][25][26][27], and is thus a promising nanoparticulate drug delivery system. Several factors affecting the characteristics of chitosan-TPP nanoparticles have been studied, such as the ratio between crosslinker and polymer [17,[20][21][22][23][28][29][30], the molecular weight of the chitosan [17,20,21,24,[26][27][28][29], the chitosan concentration [22,23,26,28,31] and the pH [19,22,28,29]. For instance, increasing the molecular weight and the concentration of the chitosan employed in the preparation of chitosan-TPP nanoparticles have resulted in the formation of larger particles [20-24, 26-29, 31].…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles presented an adequate size range (100-200 nm, depending on chitosan molecular weight, MW), a positive surface charge (+22 to +35 mV) and very high DNA association efficiency (>90%). The ability of the nanoparticles to entrap pDNA was in agreement with the previous results obtained for other chitosan-based nanometric systems, and it can be easily explained by the high affinity of chitosan for the DNA (86,87). Indeed, it is known that the strong electrostatic interaction exists between the phosphate groups of DNA and the amino groups of CS, as well as hydrophobic and hydrogen bonds (88).…”
Section: Chitosan-based Nanoparticlessupporting
confidence: 88%
“…Grafting of PEG to chitosan was carried out by a carbodiimide-mediated reaction, using a carboxylic acid derivative of PEG (MeO-PEG-OCH 2 CO 2 H) as previously reported (10,16,17). MeO-PEG-OCH 2 CO 2 H was synthesized from a commercially available MeO-PEG-OH.…”
Section: Synthesis Of Peg-g-csmentioning
confidence: 99%
“…Among them, chitosan (CS)-based carriers (both polyplexes and nanoparticles) are an appealing approach due to their interesting properties and their efficiency in delivering genetic material, including plasmid DNA (pDNA) (3), oligonucleotides (4) and siRNA (5,6). Within this context, we have recently reported the feasibility and efficacy of nanoparticles made of poly(ethylene glycol)-grafted CS (PEG-g-CS) and also those from hyaluronic acid (HA) and CS as delivery carriers for pDNA (7)(8)(9)(10). The results of this previous work indicated that the presence of either PEG or HA in the polymer nanostructure has a very positive role, not only in terms of enhancing their transfection capacity but also in terms of improving the toxicity profile of classical CS-based nanosystems.…”
Section: Introductionmentioning
confidence: 99%